Strategi Dakwah Ustadz Hanan Attaki Di Era Digital Melalui Instagram @Pesan-Trend Dalam Pembentukan Karakter Di Kalangan Remaja - Sari, Sinta Purnama; Zuhriyah, Luluk Fikri; Faqiih, Ahmad Wilayahtul (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2025)
Digital Da'wah Through Social Media: A Case Study of the Instagram Account @Pesan-Trend by Ustadz Hanan Attaki In today's digital era, social media has become a highly potential platform for conveying religious messages to the younger generation. One prominent figure who has successfully utilized social media as a medium for da'wah is Ustadz Hanan Attaki through the Instagram account @Pesan-Trend. This account adopts a contemporary and accessible approach to da'wah, appealing to the spiritual side of youth through engaging visual designs and messages that are relevant to everyday life.The content presented goes beyond religious teachings, emphasizing character development such as patience, honesty, and social awareness. This approach has proven effective in capturing the attention of young audiences and integrating Islamic values into their lifestyle.One of the account’s flagship programs is Forest Night, which combines spiritual and reflective activities in natural settings, creating a deep and memorable religious experience.Through inspirational narratives and a strategic use of media aesthetics, @Pesan-Trend introduces a new face of Islamic da'wah—moderate, inclusive, and grounded. These findings indicate that social media can serve as an effective da'wah space to positively shape youth character, as long as it is delivered in a creative, relevant, and communicative manner in line with the evolving digital culture among the younger generation.Keywords: digital da'wah, Instagram, youth character, Ustadz Hanan Attaki, Pesan-Trend